Urbanization and Locality. Strengthening Identity and Sustainability by Site-Specific Planning and Design. - (:unkn) unknown (Springer, 2016)
Based on a discussion of conflicts in the urbanization process, this book provides theoretical and practical solutions for the preservation and development of urban localities. On the basis of informative case studies, it reveals the similarities and unique aspects of urbanization in Germany and China. The process of urban growth and the future trend of locality and urbanization are also examined. The book gathers contributions from architects, landscape designers, environmental engineers, urban planners and geographers, who analyze urban issues from their individual perspectives and provide methods for preserving and developing urban localities. As such, it expresses responses to urban development trends against the backdrop of sustainability in the 21st century.
Keywords: Stadtplanung; Stadtlandschaft; Verstädterung; Siedlungsstruktur; Siedlungsentwicklung; Historische Stadt; Stadtstruktur; Stadtraum; Fallstudie; Regionale Disparität; Urbanisierung; Räumliche Disparität; Suburbanisierung; Regionale Identität; Räumliche Identität; Identitätsverlust; Urbanisierung; Bautradition; Nachhaltige Entwicklung; Städtebaulicher Denkmalschutz; Internationaler Vergleich